Prescribing of nicotine replacement therapy in and around pregnancy: a population-based study using primary care data - Dhalwani, Nafeesa N.; Szatkowski, Lisa; Coleman, Tim; Fiaschi, Linda; Tata, Laila J. (Royal College of General Practitioners, 2014)
Background Licensing arrangements for nicotine replacement therapy (NRT) in the UK were broadened in 2005 to allow prescribing to pregnant smokers. However, estimates of NRT prescribing in pregnant females in the UK are currently lacking.